Sequencing of a 'mouse azoospermia' gene panel in azoospermic men: identification of RNF212 and STAG3 mutations as novel genetic causes of meiotic arrest. Issue 6 (24th May 2019) - Riera-Escamilla, A; Enguita-Marruedo, A; Moreno-Mendoza, D; Chianese, C; Sleddens-Linkels, E; Contini, E; Benelli, M; Natali, A; Colpi, G M; Ruiz-Castañé, E; Maggi, M; Baarends, W M; et al.
Abstract: STUDY QUESTION: What is the diagnostic potential of next generation sequencing (NGS) based on a 'mouse azoospermia' gene panel in human non-obstructive azoospermia (NOA)? SUMMARY ANSWER: The diagnostic performance of sequencing a gene panel based on genes associated with mouse azoospermia was relatively successful in idiopathic NOA patients and allowed the discovery of two novel genes involved in NOA due to meiotic arrest. WHAT IS KNOWN ALREADY: NOA is a largely heterogeneous clinical entity, which includes different histological pictures. In a large proportion of NOA, the aetiology remains unknown (idiopathic NOA) and yet, unknown genetic factors are likely to play be involved. The mouse is the most broadly used mammalian model for studying human disease because of its usefulness for genetic manipulation and its genetic and physiological similarities to man. Mouse azoospermia models are available in the Mouse Genome Informatics database (MGI: http://www.informatics.jax.org/ ). STUDY DESIGN, SIZE, DURATION: The first step was to design of a 'mouse azoospermia' gene panel through the consultation of MGI. The second step was NGS analysis of 175 genes in a group of highly selected NOA patients ( n  = 33). The third step was characterization of the discovered gene defects in human testis tissue, through meiotic studies using surplus testicular biopsy material from the carriers of the RNF212 and STAG3 pathogenic variants. The final step was RNF212 and STAG3 expression analysis in a collection of testis biopsies. PARTICIPANTS/MATERIALS, SETTING, METHODS: From a total of 1300 infertile patients, 33 idiopathic NOA patients were analysed in this study, including 31 unrelated men and 2 brothers from a consanguineous family. The testis histology of the 31 unrelated NOA patients was as follows: 20 Sertoli cell-only syndrome (SCOS), 11 spermatogenic arrest (6 spermatogonial arrest and 5 spermatocytic arrest). The two brothers were affected by spermatocytic arrest. DNA extracted from blood was used for NGS on Illumina NextSeq500 platform. Generated sequence data was filtered for rare and potentially pathogenic variants. Functional studies in surplus testicular tissue from the carriers included the investigation of meiotic entry, XY body formation and metaphases by performing fluorescent immunohistochemical staining and immunocytochemistry. mRNA expression analysis through RT-qPCR of RNF212 and STAG3 was carried out in a collection of testis biopsies with different histology. MAIN RESULTS AND THE ROLE OF CHANCE: Our approach was relatively successful, leading to the genetic diagnosis of one sporadic NOA patient and two NOA brothers. This relatively high diagnostic performance is likely to be related to the stringent patient selection criteria i.e. all known causes of azoospermia were excluded and to the relatively high number of patients with rare testis histology (spermatocytic arrest). All three mutation carriers presented meiotic arrest, leading to the genetic diagnosis of three out of seven cases with this specific testicular phenotype. For the first time, we report biallelic variants in STAG3, in one sporadic patient, and a homozygous RNF212 variant, in the two brothers, as the genetic cause of NOA. Meiotic studies allowed the detection of the functional consequences of the mutations and provided information on the role of STAG3 and RNF212 in human male meiosis. LIMITATIONS, REASONS FOR CAUTION: All genes, with the exception of 5 out of 175, included in the panel cause azoospermia in mice only in the homozygous or hemizygous state. Consequently, apart from the five known dominant genes, heterozygous variants (except compound heterozygosity) in the remaining genes were not taken into consideration as causes of NOA. We identified the genetic cause in approximately half of the patients with spermatocytic arrest. The low number of analysed patients can be considered as a limitation, but it is a very rare testis phenotype. Due to the low frequency of this specific phenotype among infertile men, our finding may be considered of low clinical impact. However, at an individual level, it does have relevance for prognostic purposes prior testicular sperm extraction. WIDER IMPLICATIONS OF THE FINDINGS: Our study represents an additional step towards elucidating the genetic bases of early spermatogenic failure, since we discovered two new genes involved in human male meiotic arrest. We propose the inclusion of RNF212 and STAG3 in a future male infertility diagnostic gene panel. Based on the associated testis phenotype, the identification of pathogenic mutations in these genes also confers a negative predictive value for testicular sperm retrieval. Our meiotic studies provide novel insights into the role of these proteins in human male meiosis. Mutations in STAG3 were first described as a cause of female infertility and ovarian cancer, and Rnf212 knock out in mice leads to male and female infertility. Hence, our results stimulate further research on shared genetic factors causing infertility in both sexes and indicate that genetic counselling should involve not only male but also female relatives of NOA patients. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by the Spanish Ministry of Health Instituto Carlos III-FIS (grant number: FIS/FEDER-PI14/01250; PI17/01822) awarded to CK and AR-E, and by the European Commission, Reproductive Biology Early Research Training (REPROTRAIN, EU-FP7-PEOPLE-2011-ITN289880), awarded to CK, WB, and AE-M. The authors have no conflict of interest.